Surveying inventors listed on patents to investigate determinants of innovation - Mattes, E.; Stacey, M.; Marinova, Dora (Springer, 2006)
This paper reviews the methods and findings of studies surveying inventors on nationally representative sample of patents or patent applications. These studies show that the most common inventor is a middle-aged man with a postgraduate qualification, with women representing only 0.4% to 3.5% of inventors. They demonstrate that 43% to 68% of granted patents become innovations (52% on average). Despite such findings this body of work has only been cited 61 times in scientific journals. Thus, surveys of inventors provide good insights into the process of commercialising patents and yet are an underutilised method especially within the literature on innovation.